Kantian Grace as Ethical Gymnastics - Vanden Auweele, Dennis (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Kant’s concept of grace in Religion within the Bounds of Mere Reason is a difficult topic, exegetically speaking. Obviously enough, Kant subscribes positively to a notion of divine assistance. This appears awkward given his rationalist ethics rooted in personal autonomy. This has given cause to interpreters of Kant’s philosophy of religion – both early commentators and today – to read Kant’s account of grace is uniquely rationalist. This would make grace a rational expectation given personal commitment to good works. The argument of this paper is that grace is a hyperrationalist element in Kant’s practical philosophy because of the potentially problematic consequences of Kant’s views of human nature. Human nature is namely not particularly prone to be responsive to the rational moral law and therefore requires a number of pedagogical tools that facilitate moral agency.